2015
DOI: 10.1038/ncomms9093
|View full text |Cite
|
Sign up to set email alerts
|

A caveolin-dependent and PI3K/AKT-independent role of PTEN in β-catenin transcriptional activity

Abstract: Loss of the tumour suppressor PTEN is frequent in human melanoma, results in MAPK activation, suppresses senescence and mediates metastatic behaviour. How PTEN loss mediates these effects is unknown. Here we show that loss of PTEN in epithelial and melanocytic cell lines induces the nuclear localization and transcriptional activation of β-catenin independent of the PI3K–AKT–GSK3β axis. The absence of PTEN leads to caveolin-1 (CAV1)-dependent β-catenin transcriptional modulation in vitro, cooperates with NRASQ6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 62 publications
3
62
0
Order By: Relevance
“…We also found that knockdown of Sall4 directly increased Bmi-1 expression by activating the promoter activity of Bmi-1 in ICC cells, indicating that Bmi-1 was a direct Sall4 target gene in several types of cancers. In addition, Bmi-1 can decrease GSK3β, the component of Axin/GSK3β/APC complex, to prevent the degradation of β-catenin, leading to activation of Wnt/β-catenin signaling in breast cancer 23,24. Interestingly, β-catenin is inactivated as a substrate of AKT 24.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that knockdown of Sall4 directly increased Bmi-1 expression by activating the promoter activity of Bmi-1 in ICC cells, indicating that Bmi-1 was a direct Sall4 target gene in several types of cancers. In addition, Bmi-1 can decrease GSK3β, the component of Axin/GSK3β/APC complex, to prevent the degradation of β-catenin, leading to activation of Wnt/β-catenin signaling in breast cancer 23,24. Interestingly, β-catenin is inactivated as a substrate of AKT 24.…”
Section: Discussionmentioning
confidence: 99%
“…The long latency in these models (>10 months) indicates that additional genomic alterations are required for tumor progression. Loss-of-function mutations in phosphatase and tensin homolog (PTEN), cyclin dependent kinase inhibitor 2A (CDKN2A), or cyclin-dependent kinase inhibitor 2A (INK4A) and transformation related protein 53 (TRP53), events that are frequently observed in human melanoma (16), have been shown to increase the penetrance and reduce the latency of these BRAF V600E -and/or NRAS Q61K -driven mouse melanoma lesions (13,14,(17)(18)(19)(20). Importantly, since these melanoma lesions develop in the absence of UV exposure, the background mutation frequency is likely to be dramatically reduced.…”
Section: Q61kmentioning
confidence: 99%
“…miR-203 has been previously implicated in the pathogenesis of many tumor types including colorectal cancer [1], gastric cancer [2], breast cancer [3], melanoma [4], and liver cancer [5]. In lung cancer, miR-203 functions as a tumor suppressor which represses cell proliferation and metastasis [6] by targeting Bmi1 and PKCα [7,8].…”
Section: Introductionmentioning
confidence: 99%